The effects of SN Ps in the regions of positioning RNA polymerase II on the TBP/promoter affinity in the genes of human circadian clock - O. A. Podkolodnaya; D. A. Rasskazov; N. L. Podkolodnyy; N. N. Podkolodnaya; V. V. Suslov; L. K. Savinkova; P. M. Ponomarenko; M. P. Ponomarenko (Вавиловский журнал генетики и селекции)
Genetic variability in the genes of circadian clock is manifested as the phenotypic variability of physiological functions and behavior as well as disorders of the function of not only the clock but also other systems, leading to the development of a pathologies. We analyzed the influence of SNPs localized in the [–70, –20] region from the transcription start site of the gene on TBP / promoter affinity in two groups of genes that are components of the system of human circadian clock. The first group comprises the genes of the circadian oscillator core (11 genes); the second, the genes of the nearest regulatory environment of the circadian oscillator (21 genes). A group for comparison included genes with another function (31 genes). The SNP_TATA_Comparator web service was used for prediction of the effect of SNPs in the regions of positioning of RNA polymerase II on the dissociation constant for TBP / promoter. It was shown that the number of SNP markers reducing the TBP / promoter affinity in the first group of genes significantly lower than the number of SNP markers increasing affinity (α < 10–3). The reverse was true of the comparison group: SNP markers reduced TBP / promoter affinity to a significantly greater extent than the SNP marker increased affinity (α < 10–6). This property may be a characteristic feature of genes  of the circadian oscillator. These predictions are important for identification of candidate SNP markers of various pathologies associated with the dysfunction of circadian clock genes for further testing them in experimental and clinical studies, as well as for verification of mathematical models of the circadian oscillator.